(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
methodically correct training of physical exercises is carried out according to didactic principles. These principles come from the basic content of the educational process and reflect the fact that it is based on objective laws. Awareness and activity, exhibitionism, systematicity and sequence, simplicity, robustness are considered from such principles. In addition, the basic didactic principles also include the ideas of Science in education and loyalty to the motherland.